Road accidents to children as pedestrians: the relationship between behaviour and accident risk - Repetto-Wright, Richard John Talbot (1977)
This thesis will argue that there is a mismatch between the information children are receiving about crossing roads from parents, schools and safety programs and the information they gain from their own experiences and from their observations of adult pedestrians.